Development of Interdisciplinary STEM Impact Measures of Student Attitudes and Reasoning - Mayes, Robert; Rittschof, Kent (Frontiers in Education, 2021)
The integration of Science, Technology, Engineering and Mathematics (STEM) programs is a national trend. The goal of implementing STEM in schools is to prepare students for the demands of the 21st century, while addressing future workforce needs. The Real STEM project focused on the development of interdisciplinary STEM experiences for students. The project was characterized by sustained professional development which was job-embedded, competency-based, and focused on the development of five STEM reasoning abilities within real-world contexts. The project promoted inclusion of tasks that drew on multiple STEM disciplines, embraced the use of authentic teaching strategies, and supported development of collaboration through interdisciplinary STEM professional learning communities and engaging STEM experts from the community. The four tenets of the project are presented and research on developing and characterizing measures of student impact are provided. Key outcomes include the construction and evaluation of measures supporting interdisciplinary STEM to assess both the impact of intervention on student attitudes toward STEM and students’ STEM reasoning abilities. Findings include reliability and validity evidence supporting attitude measurement and reasoning measurement as well as exploratory results that highlight a disconnection between STEM attitudes and STEM reasoning with the interdisciplinary STEM intervention examined.